Hothouse Flower - Riley, Lucinda (London Penguin Books, 2011)
As a child Julia Forrester spent many idyllic hours in the hothouse of Wharton Park estate, where her grandfather tended the exotic flowers. So when a family tragedy strikes, Julia returns to the tranquility of Wharton Park and its hothouse. Recently inherited by charismatic Kit Crawford, the estate is undergoing renovation.
Keywords: Social isolation -- Friendship